Rosuvastatin Counteracts Vessel Arterialisation and Sinusoid Capillarisation, Reduces Tumour Growth, and Prolongs Survival in Murine Hepatocellular Carcinoma - Annemilaï Tijeras-Raballand; Patricia Hainaud-Hakim; Jean-Olivier Contreres; Caroline Gest; Carole Le Henaff; Bernard I Levy; Marc Pocard; Claudine Soria; Evelyne Dupuy (Gastroenterology Research and Practice)
Background and Aims. An arterial blood supply and phenotypic changes of the sinusoids characterise the liver vasculature in human hepatocellular carcinoma (HCC). We investigated the effects of rosuvastatin on liver vessel anomalies, tumour growth and survival in HCC. Methods. We treated transgenic mice developing HCC, characterized by vessel anomalies similar to those of human HCC, with rosuvastatin. Results. In the rosuvastatin group, the survival time was longer (P<.001), and liver weight (P<.01) and nodule surface (P<.01) were reduced. Rosuvastatin decreased the number of smooth muscle actin-positive arteries (P<.05) and prevented the sinusoid anomalies, with decreased laminin expression (P<.001), activated hepatic stellate cells (P<.001), and active Notch4 expression. Furthermore, rosuvastatin inhibited endothelial cell but not tumour hepatocyte functions. Conclusions. Rosuvastatin reduced the vessel anomalies and tumour growth and prolonged survival in HCC. These results represent new mechanisms of the effects of statin on tumour angiogenesis and a potential target therapy in HCC.